Initiation of antiretroviral therapy before detection of colonic infiltration by HIV reduces viral reservoirs, inflammation and immune activation. Issue 1 (15th September 2016) - Crowell, Trevor A; Fletcher, James LK; Sereti, Irini; Pinyakorn, Suteeraporn; Dewar, Robin; Krebs, Shelly J; Chomchey, Nitiya; Rerknimitr, Rungsun; Schuetz, Alexandra; Michael, Nelson L; Phanuphak, Nittaya; Chomont, Nicolas; et al.
Abstract : Introduction: Colonic infiltration by HIV occurs soon after infection, establishing a persistent viral reservoir and a barrier to cure. We investigated virologic and immunologic correlates of detectable colonic HIV RNA during acute HIV infection (AHI) and their response to antiretroviral treatment (ART). Methods: From 49, 458 samples screened for HIV, 74 participants were enrolled during AHI and 41 consented to optional sigmoidoscopy, HIV RNA was categorized as detectable (≥50 copies/mg) or undetectable in homogenized colon biopsy specimens. Biomarkers and HIV burden in blood, colon and cerebrospinal fluid were compared between groups and after 24 weeks of ART. Results: Colonic HIV RNA was detectable in 31 participants (76%) and was associated with longer duration since HIV exposure (median 16 vs. 11 days, p= 0.02), higher median plasma levels of cytokines and inflammatory markers (CXCL10 476 vs. 148 pg/mL, p= 0.02; TNF‐RII 1036 vs. 649 pg/mL, p< 0.01; neopterin 2405 vs. 1368 pg/mL, p= 0.01) and higher levels of CD8+ T cell activation in the blood (human leukocyte antigen ‐ antigen D related (HLA‐DR)/CD38 expression 14.4% vs. 7.6%, p <0.01) and colon (8.9% vs. 4.5%, p= 0.01). After 24 weeks of ART, participants with baseline detectable colonic HIV RNA demonstrated persistent elevations in total HIV DNA in colonic mucosal mononuclear cells (CMMCs) (median 61 vs. 0 copies/10 6 CMMCs, p= 0.03) and a trend towards higher total HIV DNA in peripheral blood mononuclear cells (PBMC) (41 vs. 1.5 copies/10 6 PBMCs, p= 0.06). There were no persistent differences in immune activation and inflammation. Conclusions: The presence of detectable colonic HIV RNA at the time of ART initiation during AHI is associated with higher levels of proviral DNA after 24 weeks of treatment. Seeding of HIV in the gut may have long‐lasting effects on the size of persistent viral reservoirs and may represent an important therapeutic target in eradication strategies.